Impacts of US interest rates on growth, income distribution, and macroeconomic policy space in developing countries: A SFC supermultiplier model - Jo\~ao Emboava Vaz (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2024)
This paper presents a stock-flow-consistent model in which growth is led by exports and government expenditure. It considers domestic and external debt dynamics and gross capital flows. Countries may choose to not fully use their external space to accumulate international reserves. The model is then applied to an exercise of comparative dynamics to look at how an external shock led by a hike in US Fed foreign interest rates may impact growth and income distribution in a developing country under different policy responses. The shock forces the country to apply at least one contractionary macroeconomic policy or lose its reserves. Countries more financially integrated may only be able to balance external accounts through contractionary monetary policy. Accumulated international reserves may help maintain expansionary policies and higher average growth rates by providing liquidity in foreign currency.
Keywords: E62; E63; F32; F43; O40; 330; Supermultiplier; Structuralism; open economy growth; macroeconomic policy space; stock-flow-consistent modelling